Exploring Just and Unjust Wars through Afrofuturism: An Interdisciplinary Approach to International Studies - Chukwuemeka, Aneke Emmanuel (Pusmedia Group Indonesia, 2025)
Understanding just and unjust wars required fresh perspectives that moved beyond traditional frameworks rooted in Western thought. This study explored such perspectives through Afrofuturism, an interdisciplinary approach that combined international studies, cultural theory, and speculative fiction. The study adopted a qualitative, interdisciplinary methodology combining literary analysis, cultural theory, and international relations. It examined key Afrofuturist works—including novels by Octavia Butler and Nnedi Okorafor, music from artists like Sun Ra and Janelle Monáe, and visual art—to uncover alternative perspectives on war, resistance, and liberation. Data collection involved reviewing these creative texts alongside scholarly literature from international relations and postcolonial studies. Using thematic content analysis, the study identified recurring themes of conflict and justice in Afrofuturist narratives and compared them with traditional theories such as realism and liberalism to reveal Afrofuturism’s unique contributions. The study examined just and unjust wars through ethical, legal, and historical perspectives alongside international relations theories and postcolonial critiques. It introduced Afrofuturism to reimagine conflict and resistance, focusing on African diaspora identity, colonial legacies, and creative expressions of liberation. Emphasizing youth, cultural memory, and empathy, the research offered insights for peacebuilding and policy in international studies. The findings demonstrated Afrofuturism’s power to deepen empathy, foster cultural resilience, and inspire global citizenship, offering transformative insights into the nature of war and peace. The research ultimately called for greater inclusion of Afrofuturist perspectives within international studies education, policy development, and peacebuilding initiatives to encourage more imaginative and inclusive approaches toward conflict resolution and social justice.